Parameter analysis of single U-tube GHE and dynamic simulation of underground temperature field round one year for GSHP. (1st May 2019) - Bi, Yuehong; Lyu, Tianli; Wang, Hongyan; Sun, Ruirui; Yu, Meize
Abstract: Based on a quasi 3-D steady model inside and a 2-D unsteady model outside of the borehole of ground heat exchanger(GHE), the relationship between the heat exchange rate per depth of borehole and main parameters (center-to-center distance of two branch pipes, radius and depth of the borehole) has been analyzed. The rational values of those design parameters with considering the heat exchange rate per depth of borehole are obtained. The dynamic simulations of underground temperature field (UTF) of single-pipe and pipe-group of U-tube GHE have been conducted by ANSYS. The change rules of UTF are obtained when ground source heat pump(GSHP) has experienced a complete cooling and heating cycle during one year. The simulation results of a single-pipe show that the action radius of borehole is 1.9 m, i.e., it is reasonable that the borehole center-to-center distance is 3.8 m. The simulation results of pipe-group indicate that temperature of the soil center encircled by four boreholes at the beginning of heating in winter is higher than the initial temperature of soil, but it is in opposite for cooling in summer, which is beneficial to the efficient operation of GSHP. This work can provide guidance for the rational design and operation of GSHP. Highlights: Relation of heat exchange rate per depth of borehole(HERPDB) with design parameters. Rational values of design parameters with considering HERPDB. Dynamic simulation of underground temperature field (UTF) of a single U-tube GHE. Dynamic simulation of UTF of pipe-group of U-tube GHE round one year. Efficient operation of GSHP with borehole center-to-center distance of 3.8 m